Sixth grade can really kill you : ...but only if you let it! - DeClements, Barthe (New York, N.Y., U.S.A. : Scholastics, 1985)
Helen fears that lack of improvement in her reading may leave her stuck in the sixth grade forever, until a good teacher recognizes her reading problem.
Keywords: Schools -- Fiction; Reading -- Fiction; Dyslexia -- Fiction; Teacher-student relationships -- Fiction